Penurunan Minat Sepak Bola di Kalangan Gen Z Pasca Pemutusan Kontrak Shin Tae-Yong: Studi Persepsi Publik di Era Digital - Nurhaliza, Siti (el-Khuwailid: Journal of Multidisciplinary Studies, 2025)
Football is one of Indonesia’s most popular sports, particularly among generation Z (gen Z), who actively engage with the national team through social media. However, the termination of Shin Tae-Yong’s contract has significantly impacted their enthusiasm. This study examines how his dismissal influences gen Z’s engagement by analyzing changes in their digital interactions and its implications for the football ecosystem. Using a qualitative phenomenological approach and social attachment theory, this study examines online discussions on Twitter, Instagram, and TikTok. The findings reveal a decline in gen Z’s engagement, reflected in reduced social media interactions and the emergence of boycott campaigns against national football. This disengagement may disrupt Indonesia’s football ecosystem, particularly by reducing match attendance, viewership, and sponsorship interest. Therefore, football stakeholders must adopt inclusive digital strategies to rebuild gen Z’s loyalty and sustain long-term fan engagement.